SUCCESS OF IMPLEMENTATION OF COMPUTER CRIME ACT (UU ITE NO.11 2008) (A Case Study in the Higher Education Institution in Indonesia) - Rizki Yudhi Dewantara (Profit: Jurnal Adminsitrasi Bisnis, 2017)
Computer crime rate grow rapidly along with the development of the digital world that has touched almost all aspects of human life. Institutions of higher education cannot be separated from the problem of computer crime activities. The paper analyses the implementation of Indonesia Computer Crime Act (UU ITE NO.11 2008) in the Higher Education Institution in Indonesia. It aims to investigate the level of computer crimes that occurred in the higher education institution environment and the act (UU ITE 11, 2008) successfully applied to prevent the crime that would arise. In this research, the analysis using Descriptive Statistics, Binary logistic regression. This paper also describes the success implementation of the Information System Security Policy (ISSP) as a computer crime prevention policy in higher education institution in Indonesia. In factor of act, clarity of objectives and purpose of the UU ITE 11, 2008 was low, the communication and socialization activities are still low to the society especially to the higher education institution, moreover the control process has been running on UU ITE 11, 2008, but at a low level.Keywords: computer crime, computer crime act, public policy implementationÂ ABSTRAKÂ Kejahatan Komputer berkembang pesat sejalan dengan perkembangan dunia digital, pada institusi perguruan tinggi tidak dapat dipisahkan dari bagian kejahatan computer. Penelitian ini merupakan analisis kesuksesan penerapan undang-undang kejahatan komputer (UU ITE 11, 2008) di institusi perguruan tinggi di Indonesia. Penelitian ini bertujuan untuk mengetahui tingkat kejahatan komputer yang terjadi pada lingkungan institusi perguruan tinggi dan kesuksesan penerapan undang-undang kejahatan komputer untuk mencegah tindakan kejahatan komputer yang mungkin dapat terjadi maupun menangani kejahatan yang sedang terjadi. Berdasarkan tujuan penelitian, digunakan pendekatan quantitative dengan beberapa uji statistic antara lain analisis statistic deskriptif, dan regresi logostik binari. Hasil penelitian menjelaskan tingkat kesuksesan penerapan kebijakan keamanan sistem informasi sebagai tindakan pencegahan kejahatan sistem informasi di Institusi perguruan tinggi di Indonesia. Hasil penelitian menyatakan bahwa rendahnya faktor undang-undang, kejelasan isi dan tujuan dari kebijakan kemanan komputer di institusi perguruan tinggi mempengaruhi tingkat kesuksesan penerapan kebijakan kemanan sistem informasi, selanjutnya proses pengendalian telah berjalan pada UU ITE 11, 2008, namun pada skala yang rendah.Kata Kunci: kejahatan komputer, undang-undang kejahatan komputer, implementasi kebijakan publikÂ